Improving the Financing Mechanisms of Cultural Tourism in Regions: The Public-Private Partnership Model - Nosirov Shuhrat Berdiqulovich (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to examine the effectiveness of Public-Private partnership (PPP) mechanisms in improving the financing sustainability of cultural tourism development in heritage-rich regions, particularly in Uzbekistan. The research focuses on identifying structural weaknesses in existing financing models and proposing an integrated PPP framework capable of enhancing tourism infrastructure, heritage conservation, and regional economic growth. Methodology: A convergent mixed-method research design was employed by integrating quantitative and qualitative approaches. Quantitative analysis was conducted using panel data regression to examine the relationship between PPP financing intensity and tourism performance across six comparator countries during 2015–2023. Qualitative analysis involved systematic literature review, comparative institutional analysis, and stakeholder consultations with government institutions, private investors, development agencies, and local communities. Results: PPP-based financing significantly improves cultural tourism performance. A 10% increase in PPP financing intensity was associated with an estimated USD 420 million increase in tourism receipts. PPP-integrated models demonstrated higher restoration cost recovery, shorter project implementation periods, improved maintenance efficiency, and stronger community participation compared to traditional state-centered financing approaches. Conclusions: The proposed Five-Pillar PPP Model provides an effective and sustainable framework for financing cultural tourism in transitioning economies. Institutional reform, risk-sharing mechanisms, community integration, and digital innovation were identified as critical determinants of successful PPP implementation. Limitations: The study was limited to six comparator countries and relied on secondary datasets, which may restrict broader generalization and statistical robustness. Contribution: This research contributes a context-specific PPP framework and KPI-based evaluation model for sustainable cultural tourism financing in developing and transitioning economies